PENGARUH PERBEDAAN KONSENTRASI EKSTRAK ETER REBUSAN DAUN SIRIH (Piper betle Linn) DALAM SEDIAAN SALEP TERHADAP SIFAT FISIK DAN DAYA ANTIBAKTERINYA - yulias ninik windriyati; esti oktaria (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2008)
ABSTRACTBetle leaves has been used as antibacteria or antiseptic and was formulated in gargle. Betel leaves extractformulated in ointment in order to practical and effective to the skin. The aim of this research is to know the influenceof difference concentration of betle leaves extract in ointment to its physical properties and antibacteria effet againtsStaphylococcus aureus.Extract was obtained from leaves of the plant by decoction and continued by extraction with ether. Ointmentwere made in fine formulas with extract concentration 0.2, 0.4, 0.6, 0.8 and 1% w/w. The ointment was tested for itsphysical properties such as consisted of homogenity, viscosity, stickness and spreadibility. Antibacterial activityagaints Staphylococcus aureus was tested by diffusion method.The result of this research shown that the ointment homogenous. The difference of extract concentration had notinfluence on their viscosity and dispersive power, however had influence on their fixed time. The ointment of betleleaves extract had antibacterial activity againts Staphylococcus aureus.Keywords: Betle leaves extract, Ointment, Physical Test, antibacteri